Theoretical backgrounds for the bionic substantiation of the parameters of the ring-cutting soil-cultivating roller working bodies - L. F. Babitsky; I. V. Sobolevsky; V. A. Kuklin; Y. N. Ismailov (Аграрная наука Евро-Северо-Востока, 2018)
Surface treatment with soil compaction is the most important technological operation that has a direct impact on the conditions of growth and development of the root system of plants, and, as a result, on the yield of cultivated field crops. To improve the efficiency of this process in the development of new forms and justification of parameters and modes of tillage devices mechanical-bionic approach should be used, which proved effective in the development of design schemes and justification of the parameters of various agricultural machines. The final result is the adaptation of the working organ, bringing it to the image of a living organism and giving it certain geometric shapes, dynamics of movement and properties of the living prototype. The methods of the General theory of systems, agricultural mechanics, continuum mechanics, integral and differential calculus are used. The initial data for reasoning the parameters are physic-mechanical properties of soils: expansion index of soils, shear modulus, coefficient of lateral expansion, and the coefficient of friction. The article substantiates the optimal shape of the working surface of the loosening elements of the ring-cutting roller. Theoretical dependences on the justification of the main design parameters of the roller are obtained. For the soil conditions of the Republic of Crimea their rational values are equal to: a placement step of loosening elements S = 160 mm, the width of the contact of loosening element of the roller with the soil b = 45...50 mm, the amount of loosening elements Z = 12 pcs., the diameter of the loosening element Dp.3= 48...54 mm, the height of the loosening element of the roller h = 42...46 mm. The kinematics of the process of interaction of loosening elements with the soil is considered and the dependence for determining the total traction resistance of the soil-cultivating ring-cutting roller is obtained.